Specialized marine exploitation on African islands: A multiproxy archaeological analysis of the Playa Chica site, Gran Canaria (11th–13th CE) - Jonathan Santana; Jacob Morales; Simon-Pierre Gilson; Aitor Brito-Mayor; María del Carmen González-Ruiz; Paloma Vidal-Matutano; Miguel del Pino-Curbelo; Idaira Brito-Abrante; Pedro Henríquez-Valido; Javier Cruz Viera; Alberto Lacave-Hernández; Carmen Rodríguez Santana; et al. (PLoS ONE, 2026)
The Canary Islands, settled by Berber communities from Northwest Africa during the first millennium CE, offer a privileged window into coastal economies and early maritime adaptations that remain poorly documented on the adjacent mainland. Playa Chica ( Sardina , Gran Canaria , Canary Islands) preserves a five-phase Indigenous occupation sequence spanning from the 6 th to the 13 th centuries CE. This study aims to test the practice of specialized marine exploitation during Phase 5 (11 th –13 th centuries CE) employing a multiproxy approach. Systematic sampling and processing of sediments has provided a large assemblage dominated by molluscs and echinoids, followed by fish remains and crustaceans. Abundant fish scales indicate intensive on-site processing. The bone industry encompasses worked goat horn cores and hundreds of horn flakes interpreted as scaling tools, along with small hooks crafted from pig canines. Seed remains include crops (barley, durum wheat, fig) and smoke-prone plants used as fuels ( Euphorbia sp., rhizomes of Cyperus sp., and elements of Pinus canariensis cones), consistent with fish drying or smoking. Low-intensity, smoke-prone fuels identified through anthracological analyses, and twenty-nine hearths reinforce this interpretation. Pottery is scarce and functionally associated with cooking, while lithics are abundant and largely locally sourced. Collectively, these findings define an activity area dedicated to the processing and preservation of marine resources, suggesting integration within coastal-inland exchange networks. As one of the most extensively sampled coastal contexts in the archipelago, Playa Chica provides critical comparative data for understanding the intensification of marine economies among Northwest African-derived populations during the late Holocene.